Genetic variability, correlation coefficient and path analysis of some quantitative traits in bread wheat - Bhushan, Bharat; Bharti, Sonu; Ojha, Ashish; Pandey, Manoj; Gourav, Shailendra Singh; Tyagi, Bhudeva Singh; Singh, Gyanendra (Journal of Cereal Research, 2013)
A study was undertaken to estimate the genetic variability, correlation and path coefficient analysis of yield and yield contributing traits in 40 wheat cultivars grown in randomized block design with three replications at Research Farm, Department of Genetics and Plant Breeding, CCS University, Meerut, during rabi season 2008-09.The analysis of variance revealed that the treatments were highly significant for all the characters. The higher magnitudes of genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) were recorded for grain yield, biological yield, productive tillers per plant and plant height. The high heritability in broad sense was estimated for all the characters except for grain filling period and test weight. High value of heritability indicates that it may be due to higher contribution of genotypic components. High heritability coupled with high genetic advance as percent of means were recorded for plant height, harvest index, biological yield and grain yield that indicated predominance of additive gene action in the inheritance of these traits. The correlation coefficients estimate showed high direct genotypic and phenotypic correlations for the test weight, biological yield, spikelets per spike and grain filling period. While, days to heading, plant height and days to maturity showed negative correlation with grain yield. Path analysis showed that harvest index had highest direct positive effect on grain yield followed by biological yield, productive tillers per plant, spikelets per spike and test weight thereby indicated that these were main contributors to the grain yield.